2018
DOI: 10.1080/15384047.2018.1450118
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian dysgerminoma in pregnancy: A case report and literature review

Abstract: The treatment strategy in women with ovarian dysgerminoma should be discussed and structured on an individual basis. If pregnancy is desired, surgical intervention undertaken in the second trimester seems to be the first choice. When chemotherapy is indicated, unless delivery can be accomplished within a few weeks of diagnosis, it should not necessarily be delayed until after delivery. Good reproductive function and high survival rate can be achieved in patients treated with conservative surgery and adjuvant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 70 publications
0
55
1
2
Order By: Relevance
“…[29,30].These effects seem to be closely related to the type of drugs, dose and chemotherapy duration. [31] In our study there is no evidence on any reproductive outcome reduction following multiple chemotherapy cycles. Similar data are reported in several papers that showed that PEB versus PVC chemotherapy for MOCGTs does not appear to affect reproduction or menstrual cycle which normalized within 6 months in 90% of cases [32][33][34].Similarly, we reported that 78% of the patients had regular menstrual cycles during and after chemotherapy, on the other side 22% patients presented amenorrhea during chemotherapy but had regular cycles 5 months after treatment.…”
Section: Methodscontrasting
confidence: 62%
“…[29,30].These effects seem to be closely related to the type of drugs, dose and chemotherapy duration. [31] In our study there is no evidence on any reproductive outcome reduction following multiple chemotherapy cycles. Similar data are reported in several papers that showed that PEB versus PVC chemotherapy for MOCGTs does not appear to affect reproduction or menstrual cycle which normalized within 6 months in 90% of cases [32][33][34].Similarly, we reported that 78% of the patients had regular menstrual cycles during and after chemotherapy, on the other side 22% patients presented amenorrhea during chemotherapy but had regular cycles 5 months after treatment.…”
Section: Methodscontrasting
confidence: 62%
“…OD can occur in women aged from 7 months to 70 years, [ 31 ] but predominantly in young pregnant women. [ 1 , 7 , 8 , 30 , 32 ] The majority of OD pregnant women usually have non-specific symptoms, [ 33 ] including the most common abdominal pain (35.3%), followed by abdominal distention (19.6%), a growing mass (19.6%), multiple symptoms (18.6%), and non-symptoms (21.6%). [ 2 ] In our study, abdominal pain was the main complaint of the patient and led to a cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant germ cell tumor (MGCT) is an extraordinary rare ovarian cancer, which occupies no >5% of all ovarian cancers [ 1 4 ] and 18% to 26% of all ovarian cancer with pregnancy. [ 5 , 6 ] MGCT mainly includes the following subtypes: ovary dysgerminoma (OD) (38.2%), yolk sac tumor (30.4%), and immature teratoma (15.7%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keimzelltumoren können extrem selten auch primär extraovariell entstehen. Fälle mit mediastinaler oder retroperitonealer Primärlokalisation sind in Fallberichten beschrieben worden [8][9][10][11][12]. Findet sich ein primär extragonadales Dysgerminom in der Schwangerschaft, handelt es sich um eine absolute Rarität.…”
Section: Introductionunclassified